Pengaruh Pariwisata terhadap Ketimpangan Pendapatan: Studi Kasus Provinsi Daerah Istimewa Yogyakarta - Bagus Adhitya; Lilis Siti Badriah; Suprapto Suprapto (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study aims to analyze the effect of tourism, working capital credit, economic infrastructure and consumption credit on income inequality in Yogyakarta Special Province. This study uses panel data from 2007 - 2018 in the Special Province of Yogyakarta. The dependent variable is income inequality and the independent variable is tourism, working capital credit, economic infrastructure and consumption credit. The results showed that tourism, working capital credit and economic infrastructure had a negative and significant effect on income inequality, while consumption credit had a positive and significant effect on income inequality in the Special Province of Yogyakarta.